Preoperative carbohydrate volume optimization in ERAS-guided minimally invasive gastrectomy: a single-blinded RCT assessing gastric residuals and metabolic safety profiles - Ma, Chaojun; Li, Zhiyuan; Fan, Xin (Frontiers in Surgery, 2025)
BackgroundBy counting the volume of gastric contents aspirated under gastroscopy after tracheal intubation, ph and monitoring some indicators in the perioperative period. To assess the effect of preoperative oral administration of different doses of carbohydrates on ERAS results in patients undergoing laparoscopic gastric cancer resection.MethodsThe present study was conducted as an investigator-initiated, randomised controlled, parallel group, equivalence trial. The study population comprised 66 patients diagnosed with gastric adenocarcinoma, who were randomly assigned to either group A or group B. Patients in group A consumed 200 ml of 5% dextrose solution 2 h prior to the operation, and patients in group B consumed 400 ml of 5% dextrose solution 2 h prior to the operation. gastric contents were suctioned through a gastroscope immediately after endotracheal intubation. The main observation indexes were preoperative gastric residual volume.ResultsThe final study analyzed 60 patients (30 in group A and 30 in group B). The baseline characteristics of the patients in both groups were comparable. There were no significant differences between the two groups in terms of residual stomach volume (36.4 ± 9.6 vs. 37.7 ± 8.8 ml, P = 0.565), pH (2.57 ± 0.49 vs. 2.62 ± 0.53, P = 0.67), variability in suction volume per aspiration (SVV: 12.69 ± 3.21 vs. 11.85 ± 2.56, P = 0.105), and incidence of postoperative complications (13.3% vs. 16.7%, P = 0.105). 13.3% vs. 16.7%, P = 0.105) Compared with Group A, there was a difference in the degree of discomfort before surgery among patients in Group B. (thirst score: 2.03 ± 1.15 vs. 1.57 ± 1.01, P = 0.049; hunger score: 3.1 ± 1.3 vs. 2.3 ± 1.1, P = 0.002).ConclusionIn gastric cancer patients undergoing elective laparoscopic radical gastric cancer surgery, consumption of 200 ml and 400 ml of carbohydrate beverages 2 h before surgery did not significantly increase gastric residual volume, acidity, or perioperative complications, and no significant differences in intraoperative hemodynamics were observed. Increasing preoperative oral intake within safe limits may further reduce thirst and hunger scores. Individualized adjustment of rehydration volume is recommended for elderly or obese patients.